Uso de larvas de Hermetia illucens (Linnaeus, 1758) (Diptera: Stratiomyidae) para bioconversão de resíduos agroindustriais e uso do frass como fertilizante - Bento, Rodrigo de Moura Manoel (2024)
In a world where population growth, production and consumption are ever increasing, theproper disposal and treatment of waste raises concern. The Black Soldier Fly [Hermetia illucens(L., 1758] (Diptera : Stratiomyidae) is a neotropical fly which naturally occurs in North and SouthAmerica, including Brazil, and is now widely spread throughout the world. It has most of itsactivity during the larval development, in which it can consume large amounts of organic matter,and presents a short life cycle with grown flies unable to cross great distances and barelyfeeding. For over 30 years H. illucens has been studied due to its potential application in wastetreatment systems, however the majority of works focus on manure and sewage sludge and aretied to international contexts. This work aimed to evaluate the effectivity of using H. illucenslarvae to transform agroindustrial waste, presenting an alternative for lessening environmentalimpacts due to its disposal. H. illucens larvae were initially reared in standard diet of 30% soymeal, 20% corn flour and 50% wheat meal under 70% relative humidity and 12:12 h photoperiod,in 25o C, until adulthood. From this first group successful mating 40 larvae were randomlyselected and transferred to each of five replication of three different nourishment treatments:brewery solid waste (malt bagasse, fine trub and rough trub), agro-industrial residues fromminimal processing system and the standard diet as control. These treatments were kept under70% relative humidity at 27oC with lightcycle of 12 h. For each, were analyzed the developmenttime from larva to pupae and pupae into adult, the conversion of nourishment into insectbiomass, the dry matter of substrate consumed, adult’s length and sexual rate withinpopulations. Statistical analyzes were made using R software (v. 4.1.2) with a significance levelof p<0,05. We found that the diet based on agro-industrial residues from minimal processingsignificantly delayed the pupation (mean 29,92 days weighted against 18,68 days for brewerywaste diet and 15,27 days for standard diet) whereas the mean larval weight were reduced bythe brewery waste food (0,136g against 0,166g for standard diet and 0,172g for minimalprocessing’s). Changes in the sex ratio weren’t noticed. The reduction in substrate dry matterand its consequential incorporation to insect biomass were both bigger in larvae under standarddiet. The development of larvae in minimal processing residue increased the duration of thelarval period, while the weight of pre-pupae was shorter when fed with beer production residue.The best bioconversion index in the minimal processing residue, and the frass coming from thedevelopment in beer producing residue and standart diet are viable as fertilizers. New Worksare necessary with different compounds to prove the effectiveness of the H. illucens asbioconversion agents to agriculture.